Digital Business Business Algorithms, Cloud Computing and Data Engineering - Patnaik, Srikanta; Yang, Xin-She.; Tavana, Madjid; Popentiu-Vlădicescu, Florin; Qiao, Feng.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This edited book presents contributions from three different areas: cloud computing, digital mess and business algorithms on a single platform, i.e. Digital Business. The book is divided into four sections: (i) Digital Business Transformation, (ii) Cloud Computing, (iii) IOT & Mobility, and (iv) Information Management & Social Media, which are part of a holistic approach to information management and connecting the value chains of businesses to derive more throughput in the entire business ecosystem. Digital business is a niche area of computer science and business management, and its dimension is vast - it includes technologies such as cloud computing, Internet of Things, mobile platforms, big data applied in areas like ERP, data mining and business intelligence. Digital technologies have also challenged existing business models and will continue to do so. One of the key driving forces is the capacity of innovation and the commercialization of information and communication technologies. Providing insights into the new paradigm of digital business, the book is a valuable resource for research scholars, academics and professionals.
Towards Algorithmic Business: A Paradigm Shift in Digital Business -- A Decentralized Business Ecosystem Model for Complex Products -- Compliance Management in Business Processes -- Sustainable Cloud Computing Realization for Different Applications: A Manifesto -- Auction Based Scheme for Resource Allotment in Cloud Computing -- M-Cloud Computing Based Agriculture Management System -- Detection and Analysis of Drowsiness in Human Beings Using Multimodal Signals -- Enhancing Security and Privacy in Enterprises Network by Using Biometrics Technologies -- Lightweight Context-Based Web-Service Composition Model for Mobile Devices -- Impact of Mobility in IOT devices for Healthcare -- Online Social Communities -- Event Detection Using Twitter Data. .
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence